2013
DOI: 10.1037/a0030570
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the ugly: A 50-year perspective on the outcome problem.

Abstract: In the middle of the 20th century, Hans Eysenck reviewed studies of psychotherapy, which consisted primarily of psychoanalytic, psychodynamic, and eclectic treatments, and concluded that psychotherapy (as opposed to behavior therapy) was not effective and was possibly harmful. In the inaugural article in Psychotherapy, Hans Strupp challenged Eysenck's conclusions and discussed how psychotherapy research should progress. Eysenck criticized Strupp's conjectures and Strupp responded. In this article, I discuss pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 97 publications
(126 reference statements)
0
24
0
Order By: Relevance
“…23,[87][88][89][90] In this study, both treatments were empirically founded and both were standardized. Although there were trends showing that more people in the CBT condition improved, the differences failed to reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…23,[87][88][89][90] In this study, both treatments were empirically founded and both were standardized. Although there were trends showing that more people in the CBT condition improved, the differences failed to reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the question that therapeutic approach works best is still being evaluated and discussed intensively up to today (Wampold, 2013). However, the stage marked by the competition between rival therapeutic approaches has been supplemented by treatment aptitude research focusing on which treatment is most appropriate for which kind of problem.…”
Section: A Short History Of Ebp and Psychotherapy Researchmentioning
confidence: 99%
“…Considering that numerous outcome studies comparing different forms of psychotherapy have found no differences in efficacy between the forms, a base assumption is that art therapy will prove to be at least as effective as other therapies (Wampold, 2013). However, psychotherapies do not only aim at symptom reduction but also have other important aims, such as changes in personality structure, emotional skills and social interaction, improved coping skills or increased self-reflection.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in process research on verbal psychotherapies, the experience of the therapy process and its outcomes are often viewed as inseparable (Mcleod, 2011;Stiles et al, 1990;Wampold, 2013). However, even if the therapeutic process and its impacts are intertwined, it is important to make explicit whether the perspective on the impacting processes is based on the therapists' or clients' experiences, because clients' views have been shown in many cases to be better predictors of outcome than therapists' views (Castonguay, 2013;Horvath & Symonds, 1991;Martin, Garske & Davis, 2000;Weinberger & Rasco, 2007).…”
Section: Introductionmentioning
confidence: 99%